Dmaic Method Approach (Define, Measure, Analyze, Improve, Control) For Analysis Of Product Disability In Sandal Smes In Cileunyi - Elsida, Dila; Gunawan, Faizal Dwi; Prasetyo, Fendi Adi; Kasih, Vica Titik; Margana, Riki Ridwan (International Journal of Psychosocial Rehabilitation, 2020)
Sandal’s UKM in Cileunyi produce sandals products which are supplied to hotels in Bandung. Quality is one thing that must be prioritized during the production process. Defects in the product are one of the risks obtained when producing sandals. Quality that does not meet this standard is a waste. This study has purposed to analyze the broken products so it can have the result for improvement that can decrease the quantity of broken products. This analysis use DMAIC (Define, Measure, Analyze, Improve, Control) method. Define phase produces factors that cause product failure and the classification of value added activity and non value added activity in the production process. Measure phase There are 3 causes of product defects, including: the results of inappropriate embossing as much as 47.95%, the results of improper cutting as much as 33.60%, and the results of screen printing strap not as much as 18.45% which shows the results of sigma level Sandal’s UKM is 3,39 s and. Phase analyze is a causal analysis of factors that cause product defects using fish bone. The improve phase is in the form of recommendations for improvement using the 5 S method. And in the control phase which is in the form of control and supervision of the implementation of the recommendations for improvements made at this Sandal SME, so that it is expected that sigma values can increase and product defects can be reduced.